The impact of servant leadership on employees attitudinal and behavioural outcomes - Brohi, Noor Ahmed; Jantan, Amer Hamzah; Qureshi, Muhammad Asif; Jaffar, Abdul Rahman; Ali, Juha; Ab Hamid, Kamal (Taylor and Francis Group, 2018)
The primary aims of this research are to test (1) if the servant leadership style of managers reduces the turnover intention of employees directly and indirectly through psychological safety and (2) if regulatory focus of employees moderates the relationship between servant leadership and psychological safety. This research answers the call by the researchers to analyse servant leadership as a stand-alone style. This study has been carried out among the schoolteachers working in private and public schools in Pakistan, a developing country in Asia. A questionnaire-based survey was conducted, and responses were collected from 255 teachers. A co-variance-based structural equation modelling approach was used to analyse the data. The salient findings are as follows: (1) servant leadership has a negative relationship with turnover intention, (2) psychological safety mediates the relationship between servant leadership and psychological safety, and (3) regulatory focus moderates the relationship between servant leadership and psychological safety. The findings are significant in strengthening the literature on servant leadership. Furthermore, theoretical and practical implications have been discussed.